INTELLECTUAL ELECTRONIC DOCUMENTATION OF TECHNOLOGICAL OBJECTS IN PLM SYSTEM - Andrey K. Tugengold; Alexander S. Tishin; Alexey F. Lysenko; Zakhar A. Tsishkevich (Advanced Engineering Research)
An innovative approach to the documentation of technological objects is presented. Recommendations and methods for the development of the intellectual passport for technological objects in PLM system, its knowledge bases, organizations, data and knowledge presentation and processing are given.